Reconstruction of the Role Islamic Boarding School Education Culture Against the Challenges of the Islamic World in the Era of Globalization - As'aril Muhajir (Qolamuna : Jurnal Studi Islam, 2021)
AbstractResponding to various realities in the era of globalization, pesantren education should remain consistent with the primary, sources of religion, namely the al-Qur'an, Hadith, and the yellow, book study while broadening insight understanding of the progress of the times. Among the pesantren cultures that need tobe maintained is a culture of discipline, a culture of independence, a culture of fair and mutual advice, and a culture of caring for the environment. These cultures are formed as a result of the santri habits constructed by the pesantren. This means that pesantren education must be maintained to remainselective, critical, and open to the emergence of globalization. Attitudes that are exclusive or dragged into the global flow can erode the identity of Islamic education itself.Keywords: culture, education; boarding school, globalization